Role of sodium tungstate as a potential antiplatelet agent - Fernández-Ruiz R; Pino M; Hurtado B; García de Frutos P; Caballo C; Escolar G; Gomis R; Diaz-Ricart M (Dove Medical Press, 2015)
Rebeca Fernández-Ruiz,1,2 Marc Pino,3 Begoña Hurtado,4 Pablo García de Frutos,4 Carolina Caballo,3 Ginés Escolar,3 Ramón Gomis,1,2,5 Maribel Diaz-Ricart3 1Diabetes and Obesity Research Laboratory, Institut d'Investigacions Biomediques August Pi i Sunyer (IDIBAPS), Rosellón, Barcelona, 2Centro de Investigación Biomédica en Red de Diabetes y Enfermedades Metabólicas Asociadas, Barcelona, 3Hemotherapy–Hemostasis, Hospital Clínic, Universidad de Barcelona, IDIBAPS, Villarroel, Barcelona, 4Institutode Investigaciones Biomédicas de Barcelona, Consejo Superior de Investigaciones Científicas, Institut d’Investigacions Biomediques August Pi i Sunyer, Rosellón, Barcelona, 5Hospital Clinic, Universitat de Barcelona, Villarroel, Barcelona, Spain Purpose: Platelet inhibition is a key strategy in the management of atherothrombosis. However, the large variability in response to current strategies leads to the search for alternative inhibitors. The antiplatelet effect of the inorganic salt sodium tungstate (Na2O4W), a protein tyrosine phosphatase 1B (PTP1B) inhibitor, has been investigated in this study.Methods: Wild-type (WT) and PTP1B knockout (PTP1B-/-) mice were treated for 1 week with Na2O4W to study platelet function with the platelet function analyzer PFA-100, a cone-and-plate analyzer, a flat perfusion chamber, and thrombus formation in vivo. Human blood aliquots were incubated with Na2O4W for 1 hour to measure platelet function using the PFA-100 and the annular perfusion chamber. Aggregometry and thromboelastometry were also performed.Results: In WT mice, Na2O4W treatment prolonged closure times in the PFA-100 and decreased the surface covered (%SC) by platelets on collagen. Thrombi formed in a thrombosis mice model were smaller in animals treated with Na2O4W (4.6±0.7 mg vs 8.9±0.7 mg; P<0.001). Results with Na2O4W were similar to those in untreated PTP1B-/- mice (5.0±0.3 mg). Treatment of the PTP1B-/- mice with Na2O4W modified only slightly this response. In human blood, a dose-dependent effect was observed. At 200 µM, closure times in the PFA-100 were prolonged. On denuded vessels, %SC and thrombi formation (%T) decreased with Na2O4W. Neither the aggregating response nor the viscoelastic clot properties were affected.Conclusion: Na2O4W decreases consistently the hemostatic capacity of platelets, inhibiting their adhesive and cohesive properties under flow conditions in mice and in human blood, resulting in smaller thrombi. Although Na2O4W may be acting on platelet PTP1B, other potential targets should not be disregarded. Keywords: sodium tungstate, protein tyrosine phosphatase 1B, platelet adhesion, antiplatelet agents